1992
DOI: 10.1016/0014-5793(92)80590-d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new mutant α‐1‐antichymotrypsin in patients with occlusive‐cerebrovascular disease

Abstract: A new mutant α‐1‐antichymotrypsin (variant ACT) was found by direct sequencing and PCR‐single strand conformation polymorphism (PCR‐SSCP). This variant ACT was a point mutation of exon V of ACT, with the substitution of Met by Val. Four out of six individuals with this variant ACT had occlusive‐cerebrovascular disease, leading to one hypothesis that there might be an association between this mutation and occlusive‐cerebrovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…All the patients and controls were unrelated Japanese. DNA was extracted from peripheral leukocytes of each subject and genotyping was performed by PCR-RFLP according to published methods (Wenham et al, 1991;Tsuda et al, 1992;Kamboh et al, 1995). The primers and enzymes for each genotyping are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the patients and controls were unrelated Japanese. DNA was extracted from peripheral leukocytes of each subject and genotyping was performed by PCR-RFLP according to published methods (Wenham et al, 1991;Tsuda et al, 1992;Kamboh et al, 1995). The primers and enzymes for each genotyping are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, association studies of ACT polymorphism (Ala ~5 Thr) and AD in Caucasian populations have reported conflicting results (Kamboh et al, 1995;Thome et al, 1995;Talbot et al, 1996). Another common structural polymorphism of ACT, Met 389 ~ Val, has been reported to occur frequently in occlusive cerebrovascular disease (Tsuda et al, 1992), but its correlation with AD has not been investigated. The aim of this study was to determine whether these two polymorphisms of the ACT gene represent markers for AD, either alone or interacting with ApoE genotypes.…”
Section: Introductionmentioning
confidence: 98%
“…Genomic leukocyte DNA was used for DNA analyses, including polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) and PCR-restriction fragment length polymorphism (PCR-RFLP), and DNA sequencing, as described previously (Tsuda et al 1992a;1992b).…”
Section: Methodsmentioning
confidence: 99%
“…Although the pathological and physiological roles of ACT are not established, it seems likely that qualitative change in ACT would result in specific diseases. We previously reported that a variant AACT (ACT Isehara-1, Met389Val, A1252G) was found frequently in patients with cerebrovascular disease (CVD) (Tsuda et al 1992a). The present study was designed to examine whether there is a direct association between ACT Isehara-1 and a particular subtype of symptomatic ischemic CVD.…”
mentioning
confidence: 99%
“…Key Words: a1-Antichymotrypsin-Dementia A1252G-PCR. Tsuda et al (1992) screened 95 individuals in a Japanese popUlation, which included healthy subjects (n = 32), individuals with AD (n = 6), and individuals with "occlusive-cerebrovascular" disease (n = 32). They identified six individuals carrying an A-to-G substitution at nucleotide base 1,252 (A1252G), which produces a Met � Val substitution at codon 389.…”
mentioning
confidence: 99%